Measurement properties of the sit-to-stand test in people with chronic obstructive pulmonary disease: Protocol for a systematic review and meta-analysis using the COSMIN guidelines. - Christopher Farley; Stuart M Phillips; Jenna Smith-Turchyn; Dina Brooks (PLoS ONE)
Introduction Characteristics of chronic obstructive pulmonary disease (COPD) can include shortness of breath, chronic cough, sputum production and reduced exercise capacity. The sit-to-stand (STS) test variations (e.g., 5-repetition STS, 30-second STS) may be appropriate outcome measures to assess exercise capacity in people with COPD. To date, the measurement properties of the various STS tests in people with COPD have not been synthesized in a systematic review since the publication of the COnsensus-based Standards for the selection of health Measurement Instruments (COSMIN) guidelines. The purpose of this proposed systematic review is to synthesize the literature of the measurement properties of the STS test variations among people with COPD. Materials and methods The review will be conducted with methods consistent with the COSMIN guidelines. Peer-reviewed publications will be included if they assessed the measurement properties (reliability, validity, responsiveness) of a STS test in community-dwelling adults with COPD. We will search six databases from inception. Study selection and data extraction will be conducted independently and in duplicate. We will assess the risk of bias using the COSMIN Risk of Bias tool, assess results against the COSMIN updated criteria for good measurement properties, and summarize certainty of evidence using the modified Grading of Recommendations Assessment, Development and Evaluation (GRADE) tool. Study results will be pooled by calculating weighted means and 95% confidence intervals or summarized narratively, as appropriate. Conclusion This will be the first systematic review to synthesize the measurement properties of the STS tests in people with COPD using the methods recommended by COSMIN. Consequently, its results will be robust and may help clinicians or researchers identify the best variation of the STS test to use in their practice.